An Alternative In Silico Method To Predict Passive Membrane Permeability Of Potential Spsb2-Inos Inhibitor - Choong, Fei Her (2024)
The SPRY (SPla and the RYanodine Receptor) domain of the SOCS (Suppressors of Cytokine Signalling)-box protein 2 (SPSB2) was found to be responsible for the proteasomal degradation of inducible nitric oxide synthase (iNOS). The knockdown of SPSB2 in mice was found to increase iNOS expression and enhance the killing of persistent pathogens such as Mycobacterium tuberculosis, suggesting that inhibitor of SPSB2-iNOS interaction is a potential anti-infective agent. To date, several peptidic SPSB2-iNOS inhibitors have been reported. These peptides (including CP2), however, were found to have poor cell permeability, resulting in their poor activities in live macrophages. Therefore, this study aimed to propose a potential cell-permeable inhibitor of SPSB2-iNOS via in silico approach. To achieve the aim, a new bicyclic peptide, CPP9CP2 was designed, and molecular dynamics (MD) simulations were used to predict its membrane permeability. Conventional molecular dynamics (MD) analysis techniques for predicting peptide translocation, such as comparing free energy profiles (PMF) and evaluating the relationship between water pore formation and peptide penetration efficiency from steered MD simulations, were applied to three cell-penetrating peptides (TAT, CPP1, and CPP9) and one known non-cell-permeable peptide, YDEGE. However, these methods proved less effective in accurately reproducing reported in vitro experimental results. Specifically, despite YDEGE being non-cell-permeable, it did not show the highest PMF value and formed water pores similarly to TAT and CPP9, making it difficult to distinguish between genuine pore formation and simulation artifacts.